2014
DOI: 10.1159/000357704
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Smoking and Placental Expression of a Panel of Genes Related to Angiogenesis and Oxidative Stress in Early Pregnancy

Abstract: Objective: Maternal cigarette smoking is paradoxically associated with a decreased risk of developing preeclampsia. Since preeclampsia is thought to be associated with altered mechanisms of angiogenesis and oxidative stress, we aim to investigate the influence of maternal smoking on the early placental expression of a panel of genes related to angiogenesis and oxidative stress. Material and Methods: We collected villous tissue samples at 6-7 and 10-11 weeks of gestation from 31 women requesting surgical termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
(51 reference statements)
1
10
0
Order By: Relevance
“…We previously reported that we could not observe any significant effects of maternal smoking in the expression levels of genes related to angiogenesis in the villous trophoblasts obtained from tissue samples obtained at six to seven weeks of gestation [28]. Since the number of samples was small in that study, in the present study, we increased the number of samples and reexamined the effects of maternal smoking on the placenta.…”
Section: Discussionmentioning
confidence: 78%
“…We previously reported that we could not observe any significant effects of maternal smoking in the expression levels of genes related to angiogenesis in the villous trophoblasts obtained from tissue samples obtained at six to seven weeks of gestation [28]. Since the number of samples was small in that study, in the present study, we increased the number of samples and reexamined the effects of maternal smoking on the placenta.…”
Section: Discussionmentioning
confidence: 78%
“…The increased birth defect risk associated with smoking after IVF compared with ICSI may also be informative with regards to the maternal response to an ICSI conceptus, as the risk of certain inflammatory conditions of first pregnancy, such as pre‐eclampsia, is reduced by smoking …”
Section: Discussionmentioning
confidence: 99%
“…Akihiko Sekizawa et al reported increased placental VEGF mRNA in first trimester placentas of smokers [17], however, when number of samples increased, no difference was found [15]. Previously, we found decreased Tie2/Ang1 in smoke exposed rat placentas of GD17 [19].…”
Section: Discussionmentioning
confidence: 84%
“…Except increased placental VEGF mRNA [17] and protein [18] were reported, alterations of VEGF system and angiopoietin system gene expression levels in smoking pregnant women placenta were seldom reported. Akihiko Sekizawa et al reported increased placental VEGF mRNA in first trimester placentas of smokers [17], however, when number of samples increased, no difference was found [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation